Synthesis of Sulfonylisoureas via Sulfo-Click Reactions - Ottenbruch, Moritz; Mohr, Fabian; Kirsch, Stefan F. (Synthesis, 2020)
The synthesis of sulfonylisoureas from thiocarbamates and sulfonyl azides via a new variant of the sulfo-click reaction is reported. Water was found to be the environmentally benign solvent of choice over various other solvents tested, and the use of any additives was not required to obtain complete conversion. The experimentally simple reaction tolerates a broad range of electron-donating and electron-withdrawing substituents attached on both the thiocarbamate and the sulfonyl azide, as shown with the synthesis of 27 sulfonylisoureas that were prepared in yields ranging from 34% to 78%.
Keywords: sulfonylisoureas; sulfonyl azides; click reactions; cycloadditions; water